Analisis Efektivitas Sistem Informasi Akuntansi Penggajian Karyawan Pada PT. Bank Pembiayaan Rakyat Al-Washliyah Medan - Yurmaini Yurmaini; Khairil Ashari (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2019)
This reseach aims to determine the effectiveness of Payroll Accounting Information Systems Employees at PT. Bank Pembiayaan Rakyat Syariah Al-washliyah Medan.  PT. Bank Pembiayaan Rakyat Syariah Alwashliyah Medan is a bank finance institution based on sharia principles that accept deposits in the form of time deposits, savings and channeling funds as BPR business. To obtain the necessary data the researcher uses descriptive method with qualitative analysis. The data source used is using primary and secondary data. While to collect data researchers using observation techniques, interviews and literature. The results of research conducted by researchers, the effectiveness of payroll accounting information systems employees at PT. Bank Pembiayaan Rakyat Syariah Alwashliyah Medan  has not run effectively yet. This can be seen from the documents used in the company is the absence of payroll slips on payroll. Companies only apply amprah salary which is listed on amprah book salary. The absence of a paycheck makes the employee unaware of how much the salary is earned and how much deductions are charged to the employee each month, making it difficult for the finance department to make a payroll report and not applying the employee's memorial and income statement as a document for the remuneration of payroll Accounting is difficult to keep a payroll journal.